Molecular characterization of Coxiella burnetii isolates. - Jäger, C. (Cambridge University Press, 1998)
Restriction fragment length polymorphism (RFLP) was used for the differentiation of 80 Coxiella burnetii isolates derived from animals and humans in Europe, USA, Africa and Asia. After NotI restriction of total C. burnetii DNA and pulsed field gel electrophoresis (PFGE) 20 different restriction patterns were distinguished. The index of discrimination for this typing system was 0.86. Comparison and phylogenetic analysis of the different RFLP patterns revealed evolutionary relationships among groups that corresponded to the geographical origin of the isolates. This finding was confirmed by genetic mapping. No correlation between restriction group and virulence of isolates was detected.